Knowledge, Attitude and Practices on Use Of Metered Dose Inhalers Among Bronchial Asthma Patients in a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Bronchial Asthma is a major public health burden that affects a large number of individuals. Inhalers are an important part for the treatment of bronchial asthma. The present study is aimed to assess the level of knowledge, attitude and practices regarding use of metered dose inhaler among bronchial asthma patients, to find out the relation between knowledge, attitude and practices on metered dose inhaler use with demographics variables and observe the skill of using metered dose inhaler among bronchial asthma patients. Materials and methods: This cross-sectional descriptive study was conducted on 100 adult patients diagnosed as bronchial asthma and were using metered dose inhaler from in and outpatient department of medicine in Chittagong Medical College Hospital during January to December 2013. Data collection was done by face to face interview through structured questionnaire. After collection, data were analysed and presented to find out demographic pattern and association of knowledge, attitude and practices towards use of metered dose inhalers. Results: Among study population, age of the patients was between 18-65 years with a mean ± SD age of 40.52 ±13.70 years. Male were 54% and female were 46% with male female ratio was 1.2:1. 58% patients were living in rural area and 32% were illiterate. Family history of bronchial asthma was present in 42% and duration of disease was 5-10 years in 48%. 62% patients were using inhaler for 1-5 years and 78% were using metered dose inhaler without spacer. The knowledge, attitude, practice and inhalation technique score were poor (68%, 64%, 80%, 38%) respectively. The mean score of knowledge, attitude, practices and inhalation technique were 9.08 ± 4.36, 9.52 ± 3.08, 4.18 ± 1.36 and 6.06 ±1.42 respectively. The knowledge score was significantly related with age, sex, residence, level of education, socio-economic status and duration of using inhaler (p0.05). There was a positive relation between attitude and age, sex, residence, level of education, socio-economic status and duration of using inhaler (p0.05). The practices score was significantly associated with age, residence, level of education, socio-economic status and duration of using inhaler p0.05). The Inhalation technique response was highly significant with sex, residence, level of education, socio-economic status and duration of using inhaler (p0.05). Conclusion: The study showed that poor Knowledge, negative attitudes and poor practices about use of metered dose inhaler among a majority of bronchial asthma patients which are more in females, illiterates, low socioeconomic and rural subjects.JCMCTA 2017 ; 28 (2) : 46-52